Economic analysis of the doctrine of separation of powers : the independence of the judiciary - Salzberger, E (1993)
This thesis attempts to apply an economic approach to deal with the positive analysis of the doctrine of separation of powers, focusing on the judicial branch of government, and more specifically on the question: why do we find an 'independent' judiciary as an almost universal phenomenon in democratic countries? The first part of the thesis sets the analytical framework - what I perceive as the broad and moderate view of the economic approach towards law - and defines the phenomenon of the independence of the judiciary to be examined - the gap between the structural independence of the judiciary and its substantive independence. It also includes a literature survey of previous work related to the economic analysis of the doctrine of separation of powers and the positive analysis of the judiciary. A theoretical discussion is in the focus of the second part. It departs from a critical view of the Landes-Posner model of the independence of the judiciary, and proceeds to offer an alternative model. The main argument of the thesis is that, in contrast to the traditional view of separation of powers, we have an independent judiciary because it is in the interests of the government of the day to maintain one. Such an institution is delegated legislative and other powers, by which politicians can maximize their self-goal choices. The third part of the thesis presents some empirical findings in an attempt to support the proposed positive model of judicial independence. A statistical approach is taken to investigate the decisions whether to promote judges from the English Court of Appeal to the House of Lords, shedding new light on attitudes of British governments towards the independence of the judiciary. A more descriptive-narrative approach is taken in the final chapter, portraying and analyzing the relations between the Israeli judiciary and the other branches of government. It is argued that the analysis of these relations lends support to the delegation theory of the independence of the judiciary.